Gifts as Psychological Outbursts, Participating Teachers as Counselors in Indonesia - Selawaisa, Sepri; Lianto, Lianto; Apandie, Chris (Darussalam: Journal of Psychology and Educational, 2023)
Researchers conducted data search for 4 months at SMA Negeri 3 Palangka Raya, specifically in Class X IPS 4 and X IPS 6. The scope of this research is education (teaching, teacher-learner and psychological). Methods of the study used qualitative methods with interview techniques through audio-visual recordings that were combined into factual solids to themes in the results and discussion sections. Results revealed diversity of narratives that showed the normalization of gifts as psychological consistency to acculturation through teachers' praxis in and out of the classroom.